Character Education Through Citizenship Education Learning at Cikampek Timur 1 Public Elementary School - Siti Muthi’ah; Nijma Adzkiya Ramadhani; Warti Sri Ariani (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Character education in Indonesia is needed, especially at the elementary school level. Various methods are carried out by the school and even carried out together with the community, especially parents to help children have good potential from a young age. In responding to the importance of character education, character education is needed through learning in elementary schools to create students who have a nationalist, responsible, critical, creative and innovative attitude. This study aims to determine the meaning of character education, goals and functions so that it can be used through the civics education learning process. The benefit of this study is that it can be used as a reference material to make it easier to recognize and shape the character of students. The method used is a literature study by collecting some of the information that has been read. The results of this study indicate that the implementation of character education is still very much needed with the citizenship education subject being able to develop character in accordance with the norms and values of Pancasila.